2010
DOI: 10.17221/1701-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the age and season of fattening period on carbon dioxide emissions from broiler housing

Abstract: AbstrAct:The quantification of emissions of greenhouse gases from human activities is of prime importance for determining the importance of their effect on the environment. The aim of this study was to test a hypothesis that the interior concentration and emission of carbon dioxide in chicken housing is impacted by the age of animals and season of fattening period. Carbon dioxide (CO 2 ) concentrations and emissions were assessed over six fattening periods in total. The major part of CO 2 seemed to have its or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 13 publications
1
8
0
1
Order By: Relevance
“…The animal CO 2 production under normal farm conditions has normally a diurnal variation of ±20% (Pedersen et al, 2008). Carbon dioxide (CO 2 ) concentrations and emissions were assessed over six fattening periods in the study of Knížatová et al (2010d). The major part of CO 2 seemed to have its origin from bird respiration with assumed production of approx.…”
Section: Carbon Dioxidementioning
confidence: 99%
“…The animal CO 2 production under normal farm conditions has normally a diurnal variation of ±20% (Pedersen et al, 2008). Carbon dioxide (CO 2 ) concentrations and emissions were assessed over six fattening periods in the study of Knížatová et al (2010d). The major part of CO 2 seemed to have its origin from bird respiration with assumed production of approx.…”
Section: Carbon Dioxidementioning
confidence: 99%
“…Air concentrations of microorganisms and noxious gases depend, among others, on bird age, type of housing system and stocking density, manure management, efficiency of ventilation, and microclimate that is primarily determined by air temperature, relative humidity and airflow rate. The concentrations of these pollutants have been increasingly investigated in intensive poultry production (12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…As visible in Figure 7.3c, 𝐶 ̅ i_NH 3 exceeded the threshold mainly in the central part of the monitored period. Although this tendency is described in literature [322], the evolution of NH 3 concentration is, to some extent, hard to predict, being influenced by litter management, environmental conditions, ventilation rates and broiler health status [329]. In Figure 7.3c, it stands out that during the first days, 𝐶 ̅ i_NH 3 was considerably below the 𝐶 ̅ lim_NH 3 .…”
Section: Analysis Of the Monitored Datamentioning
confidence: 85%
“…It has been reported that most commercial farms across Europe rear broilers at densities higher than 33 kg m −2 [321]. However, gas concentrations exceeding the limits established by the 2007/43/EC Directive have also been reported in commercial poultry houses for both NH 3 [88] and CO 2 [322].…”
Section: The Detrimental Effects Of Nh3 and Co2 On Broiler Healthmentioning
confidence: 99%
See 1 more Smart Citation